Retracted: How Do Renewable Energy, Economic Growth and Natural Resources Rent Affect Environmental Sustainability in a Globalized Economy? Evidence From Colombia Based on the Gradual Shift Causality Approach - Awosusi, Abraham Ayobamiji; Mata, Mário Nuno; Ahmed, Zahoor; Coelho, Manuel Francisco; Altuntaş, Mehmet; Martins, José Moleiro; Martins, Jéssica Nunes; Onifade, Stephen Taiwo (Frontiers in Energy Research, 2022)
Currently, the world is at the point in which energy generation and consumption are accountable for global warming and climate change. The question at the core is whether or not we want to quit generating and consuming energy? The obvious answer to this question is “no”. Therefore, the necessity for innovation is curial to attain sustainable growth from energy usage. This research specifically focused on Colombia, which represents the aforementioned threats to a large extent as the trajectory of economic expansion is characterized by significant CO2 emissions in Colombia. In this regard, we examine theassociation between globalization, renewable energy, natural re-sources rent, economic growth, and CO2 emission from 1970 to 2017. This study employed the novel Gradual Shift Causality method accounting for breaks in data to highlight the connection between the variable of concern, and FMOLS, DOLS, and ARDL estimators are used for the long-run analysis. The cointegration test confirmed a long association between the considered variables. The long-run empirical results uncovered growth-induced emissions in Colombia. The result illustrated that the path of development is unsustainable in Columbia. In contrast, global-ization and renewable energy demonstrated a favorable contribution to environmental quality. The outcomes of Gradual Shift Causality indicated that globalization, natural resource rent, and economic growth Granger cause CO2 emissions. The findings highlight the need to enact well-coordinated measures to reduce environmental deterioration in Colombia. Colombia should actively promote renewable energy development and foster a more competitive environment for renewable energy investment to mitigate environmental damage caused by economic growth.